Anemia among women of reproductive age in the Philippines and its implications in community - Agdeppa, Imelda Angeles (World Nutrition Journal, 2025)
Anemia is a persistent global problem and it affects all segments of the population from infancy, young and school children, adolescents, adults, pregnant and lactating women, and the elderly. It is more prevalent in impoverished countries. Globally, WHO estimated that in 2019, 40% of all children aged 6359 months, 37% of pregnant women and 30% of women 15349 years of age were affected by anemia. The South-East Asia Region is one of the most affected regions.